Deploying Engineering-Based Learning in High School Students STEM Learning - Abe Zeid (Athens Institute for Education and Research, 2020)
Teaching STEM concepts to today's high school students has been challenging. Span of attention is short. Students are glued to their electronic devices. They cannot appreciate the abstract method of teaching, meaning covering concepts followed by solving problems from a textbook. Research has shown that students become excited and motivated to learn STEM abstract concepts when they are related to their daily lives as applied to products and devices. Acknowledging this research finding, the question is how to change the traditional high school teaching approach to incorporate hands-on problem solving? Before we answer this question, we must bear in mind the many academic school year challenges and constraints. First, the curriculum is jammed. There is no room to add new courses. Second, it is hard to add new content to courses. Teachers must prepare students to take mandated standardized tests. Third, schools operate on tight budgets, making it hard to buy materials and supplies for student projects. One common teaching method that overcome these challenges and allow students hands-on experience is problem-based learning (PBL). A teacher using PBL assigns the students in class an open-ended problem that focuses on some STEM concepts. Students research the problem and solve it. The main advantage of PBL is that it helps students solve open-ended problems. It allows a teacher to assign a class an ill-defined problem to solve using STEM concepts. Typically, there is no one solution to such kind of a problem, unlike a science-based problem that has only one closed-form solution. The author has conceived, implemented, and tested an alternative method for PBL. It is EBL; engineering-based learning. EBL has the same spirit as PBL but it has its roots in engineering design. It is the structural nature of EBL that makes it easy and systematic to use in STEM classrooms. The structure is based on the well-known engineering design process. The paper discusses EBL in more details.